2012
DOI: 10.1111/j.1365-2435.2011.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal bryophyte productivity in the sub‐Arctic: a comparison with vascular plants

Abstract: Summary1. Arctic ecosystems are experiencing rapid climate change, which could result in positive feedbacks on climate warming if ecosystem carbon (C) loss exceeds C uptake through plant growth. Bryophytes (mosses, liverworts and hornworts) are important components of Arctic vegetation, but are currently not well represented in terrestrial C models; in particular, seasonal patterns in bryophyte C metabolism compared to vascular plant vegetation are poorly understood. 2. Our objective was to quantify land-surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 40 publications
(84 reference statements)
3
35
0
Order By: Relevance
“…We attribute this to the fact that FW1 and TW3 are groups with a very low vegetation canopy, with mossdominated vegetation and low vegetation total biomass, under which conditions the photosynthesis is driven more by soil water and temperature than by light. Similar results can be found from recent studies (Zona et al, 2011;Street et al, 2012). The results from two GPP calculation methods do not differ significantly except for FW2.…”
Section: Discussionsupporting
confidence: 90%
“…We attribute this to the fact that FW1 and TW3 are groups with a very low vegetation canopy, with mossdominated vegetation and low vegetation total biomass, under which conditions the photosynthesis is driven more by soil water and temperature than by light. Similar results can be found from recent studies (Zona et al, 2011;Street et al, 2012). The results from two GPP calculation methods do not differ significantly except for FW2.…”
Section: Discussionsupporting
confidence: 90%
“…We also underestimate LAI when the canopy includes a high proportion of closely appressed, overlapping leaves, especially Cassiope tetragona [31]. Finally, our estimate of LAI assumes that mosses do not contribute to the photosynthetic surface area despite the important contributions of moss photosynthesis to NEE [32,33]. Most of these errors in estimation of leaf area would vary in relation to species composition, and thus would appear as 'species effects' on estimates of NEE.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Euskirchen et al (2009) forcing if these changes occur on the same time scales as those studied by Euskirchen et al (2009). Bryophyte and lichen species composition may also play an important role in snow capture and melt; Street et al (2011a) observed that patches of Polytrichum spp. at Abisko were the first to thaw in the spring on account of their microtopographical position on the tops of small ridges and their low albedo (Fig.…”
Section: Norway/finland Border Fencementioning
confidence: 98%